2006
DOI: 10.1021/ja058591m
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Rhodopsin Protein Mimic

Abstract: Due to the difficulties in handling and manipulating membrane-bound proteins, such as rhodopsin, and the lack of crystallographic information on the cone opsins, we have opted to engineer a protein mimic of the transmembrane G-protein coupled receptor. Human cellular retinoic acid binding protein (CRABPII), a well studied and characterized protein, has been reengineered into a protein that now will bind retinal as a protonated Schiff base with high binding affinity (Kd = 2 nM) mimicking that of rhodopsin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
0
34
1
Order By: Relevance
“…This mutant is still capable of RA binding, though the affinity is significantly reduced (K d = 40(±4) nM) compared to WT-CRABPII (K d = 2.0(±1.2) nM). 52 Overall structure of CRABPII•RA and comparison with apo-WT CRABPII…”
Section: Changes Induced Upon R111m Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…This mutant is still capable of RA binding, though the affinity is significantly reduced (K d = 40(±4) nM) compared to WT-CRABPII (K d = 2.0(±1.2) nM). 52 Overall structure of CRABPII•RA and comparison with apo-WT CRABPII…”
Section: Changes Induced Upon R111m Mutationmentioning
confidence: 99%
“…The PCR products were transfected into JM109 competent Escherichia coli cells for plasmid maintenance. 52 General procedure for expression and purification of CRABPII clones Human recombinant CRABPII was expressed and purified as described. 47 The target gene (CRABPII/pET17b), as isolated from JM109 using Qiagen's Maxi Prep® DNA isolation kit, was transformed into E. coli strain BL21 (DE3)pLysS cells (Stratagene), according to standard protocols.…”
Section: F15w-crabpiimentioning
confidence: 99%
“…The primers and procedure are described in the supporting information of our previously published data (Crist et al, 2006;Vasileiou et al, 2007).…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
“…(Wang et al, 2012) The robustness of this family of proteins, in particular hCRBPII, to mutations was the central feature that led us to use them as templates to develop rhodopsin mimics for the purpose of investigating factors that contribute to wavelength regulation. (Crist et al, 2006; Huntress et al, 2013; Lee et al, 2012; Nossoni et al, 2014; Vaezeslami et al, 2008; Vaezeslami et al, 2006; Vasileiou et al, 2009a; Vasileiou et al, 2007; Vasileiou et al, 2009b; Wang et al, 2014; Wang et al, 2012; Yapici et al, 2015) During the preparation of mutants targeted for these studies, we observed protein bands that eluted separately on ion-exchange chromatography, but nonetheless, were the same species on SDS-PAGE. This led us to the discovery of a set of hCRBPII protein mutants capable of domain swapped dimerization.…”
Section: Introductionmentioning
confidence: 97%
“…(Cowan et al, 1993; Nossoni et al, 2014; Wang et al, 2012) Both hCRBPII and other members of this family are remarkably resilient to mutation. (Berbasova et al, 2013; Berbasova et al, 2016; Crist et al, 2006; Huntress et al, 2013; Lee et al, 2012; Nossoni et al, 2014; Vaezeslami et al, 2008; Vaezeslami et al, 2006; Vasileiou et al, 2009a; Vasileiou et al, 2007; Vasileiou et al, 2009b; Wang et al, 2014; Wang et al, 2012; Yapici et al, 2015) For example more than 150 structurally stable mutants of hCRBPII have been characterized in our lab in the course of our studies of protein-chromophore interactions. (Wang et al, 2012) The robustness of this family of proteins, in particular hCRBPII, to mutations was the central feature that led us to use them as templates to develop rhodopsin mimics for the purpose of investigating factors that contribute to wavelength regulation.…”
Section: Introductionmentioning
confidence: 99%